The theory of technological change and economic growth - Gomulka, Stanislaw (Routledge, 1990)
In this wide ranging exposition of the various economic theories of technological change, Stanislaw Gomulka relates them to rates of growth experienced by different economies in both the short and the long term. Analysis of countries as diverse as Japan, the Soviet Union and the United Kingdom demonstrates that there is an interdependence between technological change and the institutional and cultural characteristics of different countries, which can have a profound effect on their rates of growth. All of the major, relevant models are discussed, including those of Kuznets and Phelps, but throughout the emphasis is on the creation of a unified theoretical framework to help explain the impact of technological progress on both a micro and a macro scale.